The Relationship between Vocabulary Mastery and Speaking' Interest on Speech Skills in Class VII Students of SMPN 4 Bandar Lampung - Herlisa Herlisa (IJLHE: International Journal of Language, Humanities, and Education, 2018)
This research aimed to identify the understanding of the relationship of speaking interest and vocabulary in speech skill in the VII SMPN 4 Bandar Lampung. To reach the goal above, the writer used the method of correlations it meant the data is collected after all happenings arrived directly. The instruments that used in talking research data is questioner and test. Analyze technique of research data consist of analyze qualification experiment, statistic analyze and experiment technique of research hypothesis. Based on the result of research, can be concluded that: (1) there is positive relationship and significant between speaking interst and speech skill with the correlation coefficient about 0,756 and determination coefficient is (R2)= (0,756)2 = 0,572 or 57,2%; (2) there is positive relationship and significant between mastering vocabulary and speech skill with the correlation coefficient about 0,744 and determinations coefficient is (R2) = (0,744)2 = 0,554 or 55,4%; (3) there is positive relationship and significant between speaking interst and vocabulary with the speech skill by correlation coefficient is 0,840 > r table = 0,244 and determination coefficient is (r2) = 0,840)2 or 70,5%.